Studying The Role of Zinc for The Body In Liver Pathology (Progress Annals: Journal of Progressive Research, 2024)
The studies conducted provided detailed information on the biological role of zinc for the body. We separately studied the decrease in zinc in liver pathology and the effectiveness of its supplementation